The impact of the 2013 CAP reform on the decoupled payments' capitalization into land values - Pavel Ciaian; D'Artis Kancs; Maria Espinosa (Economics and Econometrics Research Institute (EERI), 2016)
Decoupled direct payments were introduced in the European Union (EU) by the 2003 CAP reform in form of the Single Payment Scheme (SPS) and the Single Area Payment System (SAPS). The 2013 CAP reform changed both the implementation of decoupled payments as well as its budget. We assess the possible effects of the 2013 CAP reform on the capitalization of decoupled payments in land rental values. Our estimates suggest that the CAP reform leads to an increase in the capitalization of decoupled payments by additional 16 cents for each EUR of decoupled payments relative to the pre-reform situation. However, there is a relatively large variation in the reform effects between MS particularly between Old Member States (OMS) and New MS (NMS). In NMS the capitalization rate slightly reduces from 76% in the pre-reform period to 72% in the post-reform period. Although, the rate is significantly lower in OMS, it almost doubles (from 20% to 39%) due to the reform. The main source of the post-reform capitalization in the EU are the entitlement stock changes accounting for 19% of total post-reform capitalization level, followed by the internal convergence of payments with 18%, the budget change (including external convergence) with 1%, and the differentiation of payments (redistributive payment) with -7%. Overall, our estimates suggest that on average in the EU, the non-farming landowners' policy gains are 25% of total decoupled payments in the post-reform period compared to 17% in the pre-reform period.
Keywords: H22; Q11; Q18; 330; Capitalization; Decoupled subsidies; CAP reform; Land market; Land prices; Land rents; EU